If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(n) = 5 + 3(n + -1) Multiply F * n nF = 5 + 3(n + -1) Reorder the terms: nF = 5 + 3(-1 + n) nF = 5 + (-1 * 3 + n * 3) nF = 5 + (-3 + 3n) Combine like terms: 5 + -3 = 2 nF = 2 + 3n Solving nF = 2 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -3n + nF = 2 + 3n + -3n Combine like terms: 3n + -3n = 0 -3n + nF = 2 + 0 -3n + nF = 2 Reorder the terms: -2 + -3n + nF = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -3n + nF = 0 The solution to this equation could not be determined.
| 8n+3(3+n)=15-6n | | x/30 | | 24=.0021x^2-0.286x+16.28 | | 7*3-5x+2=25+2x-7x-2 | | 0.2=48 | | 6cos^2(2x)-5cos(2x)+1=0 | | 3/21=2/x | | 3(2x+15)=33 | | -7+n*7=-6 | | 10x+9y=4 | | 9x+33=21x+9 | | 171=215-x | | -x+195=258 | | 4x+3=155 | | -4(7-5)-3= | | 20=3x-13 | | 5x-14=56 | | -4-3(3-4)= | | -7x/4=21 | | 2(2x/3) | | -28=-4/3x | | 3x+14=x-21 | | -312=8(5n+1) | | 3(5+7)-7= | | 4x+3x+7+x= | | x^2+7x+31=1 | | 3-4+5*6-(-4)= | | 2x+6x-7= | | 56x^2=160x+256 | | 7x-3x+9-5= | | 10(c)+100=12(c) | | 19.5(13.3-4.4x)=7.2(0.8x-11.6) |